Satisfaction of mothers with the performance of health care providers in postpartum wards of hospitals in Zahedan - Torkzahrani, Sh; Khazaiyan, S; Shaykhan, Z; Akbarzadeh, A (Advances in Nursing & Midwifery, 2010)
Background and aim The main goal of health care providers is to gain satisfaction of patients. Accordingly, one of the criteria in assessing quality of maternity care is satisfaction of mothers. The aim of this study was to determine satisfaction of mothers with the performance of health care providers in postpartum wards of selected hospitals at Zahedan. Materials and methods In this descriptive study, 72 women with normal vaginal delivery were selected via quota sampling method in two hospitals. A questionnaire completed by interview from mothers in 4 parts including demographics and satisfaction with the performance of physicians, nurses as well as other staff was used to collect data. Its validity was determined by content method and its reliability by internal consistency. Data were analyzed by SPSS 15. Findings Mean age of the subjects was 23.65±5.49. Mean amounts of satisfaction with the performance of physicians, nurses and staff were 68.32%, 60.81% and 68.40% respectively. The highest means of satisfaction were related to the knowledge and skills of physicians as well as nurses and the lowest to the conduct of physicians and responsiveness of nurses. Conclusion With respect to the proper satisfaction of mothers with the competency of clinical staff which cannot be authentically cited due to their limited information regarding professional medical services, the conduct and responsiveness should be well attended. Keywords: Satisfaction of mothers, Postpartum care, Nursing care, Staff performance. *Corresponding Author: Torkzahrani, SH. Dept. of Community Health Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences & Health Services, Tehran, Iran E-mail: zahranishahnaz@yahoo.com